Signaling Lymphocytic Activation Molecule Family Member 1 Engagement Inhibits T Cell–B Cell Interaction and Diminishes Interleukin‐6 Production and Plasmablast Differentiation in Systemic Lupus Erythematosus. Issue 1 (27th December 2018) - Karampetsou, Maria P.; Comte, Denis; Suárez‐Fueyo, Abel; Katsuyama, Eri; Yoshida, Nobuya; Kono, Michihito; Kyttaris, Vasileios C.; Tsokos, George C.
Abstract : Objective: Signaling lymphocytic activation molecule family member 1 (SLAMF1) homophilic interactions promote immunoglobulin production and T cell–B cell cross‐talk. SLAMF1 is overexpressed on T and B cells in patients with systemic lupus erythematosus (SLE). This study was undertaken to determine the role of SLAMF1 monoclonal antibody (mAb) in modulating T cell–B cell interaction and B cell activation. Methods: Anti‐IgM–prestimulated naive or total B cells from either healthy donors or patients with SLE were cocultured with autologous T cells under CD3/CD28 stimulation, in the presence or absence of the SLAMF1 mAb. Naive B cells were stimulated with anti‐IgM and CD40L in the presence of the SLAMF1 antibody. Cytokine production by CD4+ T cells and B cells was examined by flow cytometry and/or quantitative polymerase chain reaction. Plasmablast formation and T cell and B cell conjugates were assessed by flow cytometry. IgG and antinuclear antibody production was determined by enzyme‐linked immunosorbent assay. Results: SLAMF1 ligation in a human peripheral blood T cell–B cell culture system reduced the following in both healthy controls and patients with SLE: conjugate formation, interleukin‐6 (IL‐6) production by B cells, IL‐21 and IL‐17A production by T cells, and Ig and autoantibody production. Whereas the SLAMF1 mAb directly affected the function of isolated peripheral B cells by decreasing IL‐6 and Ig production in vitro, it did not affect cytokine production by isolated T cells stimulated in vitro. Conclusion: The SLAMF1 antibody inhibits T cell–B cell interaction and suppresses B cell cytokine production and differentiation, thereby acting as a potential therapeutic tool in the treatment of patients with SLE.